ESTIMATION OF AGE AND GROWTH OF THE INDIAN OILSARDINE, SARDINELLA LONGICEPS VAL - Raja, B T Antony (Indian Journal of Fisheries, 2011)
Estimates of age and rate of growth of the Indian oil-sardine, Sardinella longiceps Valenciennes, have been made through a study of length frequency distributions obtained during the seasons from l%l-62 to 1965-66 at Calicut. With the availability of very small juveniles, a lifetime growth curve of the fish has been constructed and evidences advanced to prove that the commercial fishery of juveniles belong to O-year class. It is estimated that a growth of about 60-65 mm is attained in one month and about 95-110, 110-125, 125-140, 150-160 and 170-180 mm in 2, 3, 6, 12 and 24 months respectively. Although in rare instances the fish may live up to 3 years, the normal life span is found to be about 2 years